Meningkatkan kemampuan sikap lilin senam lantai melalui metode mengajar menggunakan bantuan tembok SD Inpres Biromaru - Gunawan, Gunawan; Fatimah, Fatimah; Humaedi, Humaedi; Daipaha, Muh. Tris Maulana (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
The PJOK learning method at SD Inpres Biromaru is still conventional, without variations in techniques or supporting media to help students successfully learn the movement. This has an impact on fourth-grade students who are unable to perform the candle pose (shoulder stand) with the correct technique, resulting in their performance being considered incomplete based on the minimum mastery criterion (KKM) of 70 set by the school. This study aims to determine efforts to improve candle pose skills through the use of instructional aids among fourth-grade students at SD Inpres Biromaru. The method used was a descriptive method with a classroom action research (CAR) design. The research subjects consisted of 18 fourth-grade students. Data analysis was carried out using the percentage of mastery achievement. The results showed that in the pre-cycle stage, the lowest student score was 50.00 and the highest was 76.67, with an average of 64.62. In Cycle I, the lowest score increased to 60.00, the highest to 83.33, and the average to 72.55. In Cycle II, the lowest score reached 63.33, the highest 90.00, and the average 76.37. The percentage of student mastery in the pre-cycle was 22.16% (4 students), increased to 27.72% (5 students) in Cycle I, and reached 61.76% (21 students) in Cycle II. Overall, the mastery level reached 77.76% or 14 students, which falls into the moderate category.